Desvio de função dos servidores técnico-administrativos em educação : um estudo no Centro de Ciências Exatas da Universidade Federal do Espírito Santo - Souza, Renato Pessotti de (2017)
This research paper aims at presenting an analisys of job function deviations among administrative public servants within Centro de Ciências Exatas (CCE), in Universidade Federal do Espírito Santo (UFES). Based on Law 11.091, of January, 12, 2005, this study discussed the impact of job function deviations over Personnel Management within public organizations, particularly in the Federal Institutions of Higher Education (IFES). According to a theoretical approach, the concepts in the field of personnel management, job function deviations, career and encouragement in the working environment concerned were considered. A qualitative research was done and it was defined as descriptive and bibliographical. The field procedures involved the collection of documentos and bibliograhical material, as well as open ended interviews with workers. The results revealed the existence of cases of job function deviation for different reasons. In the end, the use of such methodology for this research is suggested to be applied in UFES so as to contribute to the mapping of the ocurrence of job function deviations and help to correct such ocurrences. As end product, a proposal of a pilot project was submitted to the Personnel Management Dean’s Office (Pró-Reitoria de Gestão de Pessoas). This projecrt can be applied within all the University